1983
DOI: 10.1002/cne.902130202
|View full text |Cite
|
Sign up to set email alerts
|

A type of aspiny neuron in the rat neostriatum accumulates [3H]γ‐aminobutyric acid: Combination of golgi‐staining, autoradiography, and electron microscopy

Abstract: Light microscopic autoradiography was used to identify cells in the neostriatum that became labelled after the local injection of [3H]gamma-aminobutyrate (GABA). The GABA-accumulating cells comprised up to 15% of the total population of neurons. Thirty-seven of these cells were examined in the electron microscope and it was found that they all had similar cytological characteristics, i.e., prominent nuclear indentations, a moderate volume of cytoplasm, rich in organelles, and sparse synaptic input to the perik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
1

Year Published

1983
1983
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(71 citation statements)
references
References 77 publications
7
63
1
Order By: Relevance
“…Based on previous morphological descriptions of striatal neurons (DiFiglia et al, 1976;Bishop et al, 1982;Bolam et al 1983), the aspiny TH-i cells we and others have seen (Iacovitti, 1991;Ostergaard et al, 1991; best correspond to GABAergic, aspiny neurons. Our double-label studies with antibodies to TH and GAD provide the first indication that TH-i cells in the primate striatum are also GABAergic.…”
Section: Phenotype Of Th-i Cells In the Striatum Of Mptp-lesioned Monmentioning
confidence: 61%
See 1 more Smart Citation
“…Based on previous morphological descriptions of striatal neurons (DiFiglia et al, 1976;Bishop et al, 1982;Bolam et al 1983), the aspiny TH-i cells we and others have seen (Iacovitti, 1991;Ostergaard et al, 1991; best correspond to GABAergic, aspiny neurons. Our double-label studies with antibodies to TH and GAD provide the first indication that TH-i cells in the primate striatum are also GABAergic.…”
Section: Phenotype Of Th-i Cells In the Striatum Of Mptp-lesioned Monmentioning
confidence: 61%
“…The other subtype includes the medium, aspiny neurons that can be further subdivided into two types. One uses GABA as a transmitter (Bolam et al, 1983;Oertel and Mugnaini, 1984;Smith et al, 1987;Pasik et al, 1988;Kita, 1993), is specifically stained with antibodies to parvalbumin (Gerfen et al, 1985;Cowan et al, 1990;Kita et al, 1990), and has a round or oval-shaped cell body, 8 -15 m in diameter, with two or three varicose dendrites extending from the soma (DiFiglia et al, 1976;Bishop et al, 1982). The other type of medium, aspiny interneuron is characterized by a fusiform cell body that stains for somatostatin, neuropeptide Y, or nitric oxide synthase (Vincent et al, 1983a,b;Smith and Parent, 1986;Dawson et al, 1991).…”
Section: Abstract: Striatum; Dopaminergic Cells; Parkinson's Diseasementioning
confidence: 99%
“…The results obtained with the competitive GABA uptake inhibitor ACHC show that the perikaryal labeling in our experiments occurs by an active uptake process. ACHC also prevented labeling of the perikarya by [3H]GABA in a study of rat neostriatum (25). Further evidence for the specificity of [3H]GABA uptake comes from separate experiments in the cerebellum (13,26,28) and in the olfactory bulb (29,30) showing that the type of neuron that accumulates [3H]-GABA also contains GluDCase.…”
mentioning
confidence: 99%
“…The ability of medium-sized aspiny neurons to take up radiolabeled GABA showed that at least some of these were GABAergic (Bolam et al, 1983). Subsequent studies utilizing immunocytochemical labeling revealed three distinct types of GABAergic interneurons that colocalized, respectively, parvalbumin (PV), calretinin (CR) or neuropep-tide Y (NPY), somatostatin (SOM) and nitric oxide synthase (Takagi et al, 1983;Cowan et al, 1990;Bennett and Bolam, 1993;Kawguchi, 1993;Rymar et al, 2004).…”
Section: Interneuronal Gabaergic Inhibition In Striatummentioning
confidence: 99%